IMPACT OF COVID-19 ON NEONATAL OUTCOMES: A SYSTEMATIC REVIEW - Stevenie (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2023)
The COVID-19 infection is a pandemic that is still continuing strong and is marked by significant morbidity and fatality rates. In order to make effective use of the resources that are available, it is imperative that clinical and biochemical predictors of the severity and mortality associated with COVID-19 infection be identified as quickly as possible. Although it is impossible to be certain, there is a possibility that the SARS-CoV-2 virus can be passed on from mother to child. This transmission, however, has not been confirmed. This relationship discusses the potential interpretation of these results in terms of the effects of SARS-CoV-2 on the placenta and the pathophysiology of pregnant women. It also shows the spectrum of pathological findings from pregnant women with COVID-19 based on the infection status of their infants. Significant variation may be seen in the spectrum of pathological abnormalities between the placentas of pregnant women infected with COVID-19 and those of newborns who were not infected. The severity of maternal sickness or foetal impairment does not entirely explain the high frequency of preterm births and caesarean deliveries as well as the low incidence of breastfeeding that was found in this study. The maternal and perinatal results of COVID-19 infection during pregnancy are not marked by a severe clinical course and are, in fact, rather favorable. At this time, there is no convincing evidence that COVID-19 can be passed from person to person by the vertical route.